Population fluctuation and dispersion patterns of apple snails, Pomacea spp. (Gastropoda: Ampullariidae) in a rice ecosystem - Gilal, Arfan Ahmed; Muhamad Awang, Rita; Omar, Dzolkhifli; Abd Aziz, Nor Azwady; Gnanasegaram, Manjeri (Universiti Putra Malaysia Press, 2016)
A field study was conducted for two consecutive rice-growing seasons from August, 2013 to May, 2014 to understand the population dynamics of exotic apple snails, Pomacea spp. (Ampullariidae), as affected by ambient weather and aquatic weeds. A one-acre rice field was divided into four blocks and eight samples per block were taken using a 0.5x0.5m quadrat. Collected snails were recorded as numbers of egg clutches, juveniles, adult females and males. Average rainfall, relative humidity, temperature and water pH, along with number of aquatic weeds and seedlings, were also recorded. Results confirmed the presence of only Pomacea maculata. The numbers of egg clutches, juveniles and adults were relatively high during the off-season as compared to the main-season. Meanwhile, relative humidity had a significant effect on the number of egg clutches, and rainfall affected the densities of juveniles and adults. Among the weeds, Limnocharis flava (Alismataceae) had significant effect on the densities of different snail stages. Different stages showed uniform dispersion pattern during both seasons due presumably to continuous availability of water and abundant food. Thus, results obtained could be helpful in understanding the population dynamics of P. maculata and devising appropriate management strategy.